Fletcher Ayres: capstone - Ayres, Fletcher, artist (Colorado State University. Libraries, 2024)
The artist's statement: As a graphic designer, I am deeply inspired by the interplay between perception and meaning. The objects and forms around me are not things I just observe; they are methods of understanding, rich with personal interpretations. My work acts as a translation of these perceptions, making the invisible visible, the mundane extraordinary. By embracing brutalist and architectural aesthetics, I uncover the skeletal structures of our environment—the building blocks that shape our everyday but are seemingly always missed. Brutalism resonates with me because of its honesty and unapologetic nature. It mirrors my approach to communication: bold and direct. Whether creating for myself or a client, I remain true to these principles. Each piece of work becomes a narrative about connection—how influences interweave in digital spaces, forming a continuum of shared and personal meaning. My work does not seek to persuade or dictate; instead, it offers a mirror, inviting viewers to reflect on the structures that define their lives and relationships. Through this lens, I spark curiosity about the often-overlooked aspects of the world and ourselves. By presenting forms stripped to their concept, I challenge others to see beyond the obvious, to contemplate the underlying framework of the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design